2014
DOI: 10.2337/db14-0582
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AMPK Activation by CD36 Links Fatty Acid Uptake to β-Oxidation

Abstract: Increases in muscle energy needs activate AMPK and induce sarcolemmal recruitment of the fatty acid (FA) translocase CD36. The resulting rises in FA uptake and FA oxidation are tightly correlated, suggesting coordinated regulation. We explored the possibility that membrane CD36 signaling might influence AMPK activation. We show, using several cell types, including myocytes, that CD36 expression suppresses AMPK, keeping it quiescent, while it mediates AMPK activation by FA. These dual effects reflect the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(167 citation statements)
references
References 23 publications
7
159
1
Order By: Relevance
“…A recent report showed that a metabolite of branch chain amiof several PPAR and insulin signaling pathway genes such as Pparα and Glut1 were increased in hearts of EC-Cd36 -/-mice, while Fas and Ampk expression levels were decreased ( Figure 8C). Hearts from CM-Cd36 -/-mice, like those from germline Cd36 -/-mice, had higher Ampk mRNA levels (Supplemental Figure 8A) (10,23). This contrasted with lower Ampk levels in hearts from EC-Cd36 -/-mice ( Figure 8A), perhaps reflecting greater glucose uptake.…”
Section: Cd36 Deletion In Ecs Reducesmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent report showed that a metabolite of branch chain amiof several PPAR and insulin signaling pathway genes such as Pparα and Glut1 were increased in hearts of EC-Cd36 -/-mice, while Fas and Ampk expression levels were decreased ( Figure 8C). Hearts from CM-Cd36 -/-mice, like those from germline Cd36 -/-mice, had higher Ampk mRNA levels (Supplemental Figure 8A) (10,23). This contrasted with lower Ampk levels in hearts from EC-Cd36 -/-mice ( Figure 8A), perhaps reflecting greater glucose uptake.…”
Section: Cd36 Deletion In Ecs Reducesmentioning
confidence: 93%
“…LCFA binding to the CD36 ectodomain is followed by FA transfer to the plasma membrane through an internal tunnel that runs the length of the protein, as shown by the crystal structure of the CD36-LCFA complex (8). CD36 also functions as a LCFA sensor, influencing activation of PPARs (9) and AMPK (10).…”
Section: Introductionmentioning
confidence: 99%
“…AMPK activation by AMP in low energy states inhibits ACC and reduces malonyl CoA levels (thereby relieving inhibition of CPT1) and increases FA entry into the mitochondria to be oxidized by the β-oxidation machinery. AMPK also recruits CD36 to the sarcolemma, increasing cellular FA uptake (Samovski, et al, 2015).…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%
“…Recently, CD36 was shown to negatively regulate AMPK (45), which phosphorylates and decreases ACC activity. Decreased AMPK and p-ACC raises the possibility that malonyl CoA, produced by ACC, plays a role in decreased FA oxidation in the muscle of EK mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Samovski et al (45) suggested that CD36 suppresses AMPK activation (assessed as p-AMPK/AMPK) but fatty acids relieve this inhibition. We assessed AMPK activation in muscle of EK and WT mice and found that AMPK activity is reduced in EK muscle (Fig.…”
Section: Effects Of the Ek Mutation In Ca V 11 On Energy Expenditure-mentioning
confidence: 99%